Penerapan Metode EOQ dalam Mengendalikan Persediaan Barang - Tazkiyah, Anissa Ayuning; Muzayanah, Fety Nurlia (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the warehouse system at Fadhilah Fashion and to compare it with the application of the Economic Order Quantity (EOQ) method for controlling merchandise inventory in order to enhance effectiveness. The research was conducted within the warehouse operations of the Fadhilah Fashion enterprise. Employing a descriptive-quantitative research design, the sample comprised clothing items in category A for the 2024 period. This sampling was determined through the ABC classification method due to the wide range of apparel stocked by Fadhilah Fashion. The results of the inventory-control data analysis indicate that the implementation of the EOQ method optimizes both order quantity per replenishment and annual ordering frequency when compared to the existing warehouse system. Furthermore, EOQ contributes to total inventory cost savings and establishes appropriate safety stock levels for triggering reorders.